Frequency and characteristics of MRI-negative myelitis associated with MOG autoantibodies. (February 2021) - Sechi, Elia; Krecke, Karl N; Pittock, Sean J; Dubey, Divyanshu; Lopez-Chiriboga, A Sebastian; Kunchok, Amy; Weinshenker, Brian G; Zalewski, Nicholas L; Flanagan, Eoin P
Background: Myelitis accompanied by a negative spinal cord MRI may lead to diagnostic uncertainty. Objective and Methods: We retrospectively investigated the frequency of negative spinal cord MRI (performed <6 weeks from onset) in Mayo Clinic patients with myelin oligodendrocyte glycoprotein (MOG)-IgG-associated myelitis (2000–2019). Results: The initial spinal cord MRI was negative in 7/73 (10%) patients, despite severe acute disability (median EDSS, 7 (range, 4.5–8)); myelitis symptoms/signs were frequent (paraparesis, neurogenic bladder, sensory level, Lhermitte's phenomenon). Myelitis lesions became overt at follow-up MRI in three patients. Conclusions: A negative spinal cord MRI should not dissuade from MOG-IgG testing in patients with acute/subacute myelitis.